What happens in the ballroom - Jeffries, Sabrina (Jeffries, Sabrina. Designing debutantes., 2023)
"When members of the ton's elite need to host a dazzling party, they call upon the planning services of Elegant Occasions--three young ladies who've put their talents for fashion, food, and music to excellent use. But while they excel in designing the perfect social event, love refuses to abide by any plan"--